ABOUT THE INFLUENCE OF ELECTRIC CURRENT ON THE MECHANICAL CHARACTERISTICS OF THE STEEL RAIL - Novohrudskyi, L. S.; Opravkhata, M. Ya.; Zaitseva, L. V. (Science and Transport Progress, 2008)
In the paper the results of studies of mechanical properties of rail steel after its long-term operation are presented. The values of steel mechanical properties in transverse and longitudinal direction relative to rolling are given. It is demonstrated that the electric current modifies the mechanical properties of rail steel.